Emotion Control Education in the New Normal Era Through Riyadlah Dhikr - Hasbiyallah Hasbiyallah; Faznah Faznah; Arum Ningsih (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2022)
The COVID-19 pandemic has attacked the fabric of human life. However, activities must continue, including in the field of education. This event is known as the